1984
DOI: 10.1002/ana.410160211
|View full text |Cite
|
Sign up to set email alerts
|

Activity of multiple sclerosis during pregnancy and puerperium

Abstract: The influence of pregnancy on multiple sclerosis was studied in 338 women by determining in each trimester of pregnancy and post partum the number of relapses and the corresponding relapse rate. Eighty-five relapses occurred in association with 199 pregnancies, most (65) in the postpartum period, and a low number of relapses (2) were recorded in the last trimester of pregnancy. Comparing the average exacerbation rate of the study group with that of patients with multiple sclerosis in Israel (0.28 relapses per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(43 citation statements)
references
References 14 publications
2
38
0
3
Order By: Relevance
“…Pregnancy also offers protection to female animal models with EAE [15,36,43,61,83]. Specifically, pregnant SJL and C57BL/6 mice showed a disease amelioration compared to non-pregnant controls.…”
Section: Pregnancy In Ms and Eaementioning
confidence: 99%
“…Pregnancy also offers protection to female animal models with EAE [15,36,43,61,83]. Specifically, pregnant SJL and C57BL/6 mice showed a disease amelioration compared to non-pregnant controls.…”
Section: Pregnancy In Ms and Eaementioning
confidence: 99%
“…The most common anaesthetist’s concern is exacerbation of the pre‐existing deficit after surgery or delivery. However, any stressful condition, fever/hyperpyrexia, infection, surgery, delivery and fatigue may cause exacerbations or relapses, making it very difficult to separate the effects of these factors and anaesthetic techniques or drugs used (34). Pregnancy itself seems to cause partial remission as in other immunological diseases whereas exacerbations are possible up to 3 months after delivery.…”
Section: Sclerotic Diseasementioning
confidence: 99%
“…Natural course studies in MS have shown that the relapse rate during pregnancy, especially in the third trimester, decreases more than under treatment with currently approved first line treatments interferon-beta or glatiramer acetate. During the first three months post-partum an increase of the relapse rate follows before returning to the pre-pregnancy rate [1][3]. In general, the lower relapse rate during pregnancy might be due to a pregnancy-associated down-regulation of cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 97%